(untitled) (Journal of Plant Disease Sciences, 2025)
Marigold (Tagetes spp.) is a widely cultivated commercial flower crop in South Gujarat. However, its yield is significantly impacted by leaf spot and flower blight, primarily caused by Alternaria tenuissima.This study aimed to examine the epidemiological factors influencing disease incidence under natural field conditions at the Floriculture Research Farm, NAU, Navsari, during Kharif seasons of 2020 and 2021. The experiments were conducted on the Punjab Gainda-1 variety.